Evaluation of the Discriminatory Power of Variable Number of Tandem Repeat Typing of Mycobacterium bovis Isolates from Southern Africa. (31st October 2013) - Hlokwe, T. M.; van Helden, P.; Michel, A.
Summary: The usefulness of variable number tandem repeat (VNTR) typing based on limited numbers of loci has previously proven inferior compared to IS 6110 ‐RFLP typing when applied to the study of the molecular epidemiology of bovine tuberculosis (BTB) in both livestock and wildlife in southern Africa. In this study, the discriminatory power of 29 published VNTR loci in the characterization of 131 Mycobacterium bovis strains isolated predominantly from wildlife and a smaller number from livestock in southern Africa was assessed. Allelic diversities calculated when loci were evaluated on a selected panel of 23 M. bovis isolates with identified varying degrees of genetic relatedness from different geographic origins as well as M. bovis BCG ranged from 0.00 to 0.63. Of the 29 loci tested, 13 were polymorphic (QUB 11a, QUB 11b, QUB 18, ETR‐B and ‐C, Mtub 21, MIRU 16 and 26, ETR‐E, QUB 26, MIRU 23, ETR‐A, and Mtub 12). In addition, a comparative evaluation of the 13 loci on a panel of 65 isolates previously characterized by IS 6110 restriction fragment length polymorphism (RFLP) typing and further evaluation on 41 isolates with no typing history from Kruger National Park (KNP) highlighted that M. bovis from epidemiologically unrelated cases of BTB in different geographic regions can be adequately distinguished. However, there is a need for improvement of the method to fully discriminate between the parental KNP strain and its clones to allow the detection of evolutionary events causing transmission between and within wildlife species.